2022
DOI: 10.3389/fpls.2022.855900
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Rescues Photosynthesis and Triggers Antioxidant Defense Response in Cucumis sativus Plants Challenged by Low Temperature and High Humidity

Abstract: Environmental factors such as low temperature (LT) and high humidity (HH) hinder plant growth and development in plastic tunnels and solar greenhouses in the cold season. In this study, we examined the effect of melatonin (MT) on shoot-based tolerance to LT and HH conditions in cucumber (Cucumis sativus) seedlings and explored its underlying mechanism. LT and HH stress inhibited growth and biomass accumulation, produced leaf chlorosis, led to oxidative stress, lowered chlorophyll and carotenoid contents, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In the present study, pretreated with MT, although the and H 2 O 2 contents in pepper leaves under LL stress were obviously higher than those under CK, but significantly decreased after 6, 12, 24, 48, and 168h compared with LL, which indicated that exogenous MT effectively alleviated the LL-induced damage in pepper plants. Our results are consistent with those of a previous study that in “Zhongnong 37” cucumber ( Cucumis sativus L.) sprayed 200μM MT for 5 days during 2-leaf stage, a significant decrease of 246.1% in MDA contents were observed on 6th day under 15/10°C and 95% humidity, in addition, the H 2 O 2 contents were greatly reduced on the second and fourth day, and the production of was dramatically suppressed, compared to the seedlings without MT treatment ( Amin et al., 2022 ). Membrane stability damage is considered to be a dominant stress caused by low temperature combined with low light as indicated by the accumulations of H 2 O 2 and .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In the present study, pretreated with MT, although the and H 2 O 2 contents in pepper leaves under LL stress were obviously higher than those under CK, but significantly decreased after 6, 12, 24, 48, and 168h compared with LL, which indicated that exogenous MT effectively alleviated the LL-induced damage in pepper plants. Our results are consistent with those of a previous study that in “Zhongnong 37” cucumber ( Cucumis sativus L.) sprayed 200μM MT for 5 days during 2-leaf stage, a significant decrease of 246.1% in MDA contents were observed on 6th day under 15/10°C and 95% humidity, in addition, the H 2 O 2 contents were greatly reduced on the second and fourth day, and the production of was dramatically suppressed, compared to the seedlings without MT treatment ( Amin et al., 2022 ). Membrane stability damage is considered to be a dominant stress caused by low temperature combined with low light as indicated by the accumulations of H 2 O 2 and .…”
Section: Discussionmentioning
confidence: 57%
“…The key enzyme-encoding genes ( CsSOD , CsPOD ) were dramatically upregulated at day 2, 4, and 6, and the highest expression level was obtained at day 4, increasing by 69.25 and 95.33% in comparison with those of seedlings without MT. However, CsCAT increased from day 0 to day 6 ( Amin et al., 2022 ). In our experiment, MT pretreatment exerted slight effects on the SOD, POD, and CAT activities under control condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplification conditions included an initial step at 94°C for 2 min (1 cycle), followed by 40 cycles of 94°C for 30 s, 55°C for 30 s, and 72°C for 30 s, and a final extension at 72°C for 1 min (1 cycle), using the CFX96 Touch qRT‐PCR system (BioRad). Three technical replications were performed, and the relative gene expression was determined using the 2 −ΔΔ Ct method (Amin et al, 2022). The primers used are given in the Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in SNAT1 -deficient Arabidopsis , the gene expression of chloroplast heat shock proteins ( CpHSP70.1 and CpHSP70.2 ) and caseinolytic proteases ( ClpR1 , ClpR4 , and ClpP1 ) is suppressed, while exogenous melatonin application reverses this response, implying that melatonin might participate in the quality control of chloroplast proteins ( Lee and Back, 2018 ). Under the combined stress of low temperature and high humidity, melatonin pretreatment promotes the uptake and translocation of N, Mg, and Fe, which are responsible for chlorophyll biosynthesis and other physicochemical reactions ( Amin et al., 2022 ). Evidence indicates that, when tomato is exposed to darkness for 4 days, melatonin increases the chlorophyll content, Fv/Fm value, and starch content and ameliorates carbon starvation-induced leaf chlorosis by activating the expression of miR171b or inhibiting glucan water dikinase gene expression ( Wang et al., 2022b ).…”
Section: Melatonin Functions Against Abiotic Stressmentioning
confidence: 99%